Ideological asepsis and 'Urban design' (Ciudades, 2018)
In the discussion on the Urban Project there exists a tendency to conceive the project as a drill, as an attempt at both a morfological and social attempt, production of a satisfactory space or reproduction of certain constituent elements of 'good urban form'.
Keywords: urban project; urban design